The Role of Convergent Media in Maintaining Public Trust During the Political Year in Indonesia - Dharmajaya*, M. Agung; Setiawan, Asep (Riwayat: Educational Journal of History and Humanities, 2023)
Convergent media plays an increasingly important role in shaping people's views and understanding of politics. The purpose of this study is to understand the role of convergent media in maintaining public trust in a political year. This research was conducted using qualitative research methods. The data collection technique in this research is a literature study that has been indexed by Google Schoolar. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and conclusion drawing. The results showed that convergent media has an important role in maintaining public trust in the political year. Convergent media can act as providers of accurate and balanced information, providers of space for the public to participate in the political process and guardians of media independence.